Reciprocal loop of hypoxia‐inducible factor‐1α (HIF‐1α) and metastasis‐associated protein 2 (MTA2) contributes to the progression of pancreatic carcinoma by suppressing E‐cadherin transcription. Issue 3 (1st June 2018) - Zhu, Shuai; Deng, Shijiang; He, Chi; Liu, Mingliang; Chen, Hengyu; Zeng, Zhu; Zhong, Jianxin; Ye, Zeng; Deng, Shichang; Wu, Heshui; Wang, Chunyou; Zhao, Gang
Abstract: Metastasis‐associated protein 2 (MTA2) is overexpressed in certain malignancies, and plays important roles in tumour metastasis and progression. The present study highlights the function of MTA2 in pancreatic carcinoma through its role as a deacetylator of hypoxia‐inducible factor‐1α (HIF‐1α) and a cotranscriptional factor for E‐cadherin expression. We found that overexpression of MTA2 promoted, and knockdown of MTA2 inhibited, the invasion and proliferation of pancreatic carcinoma cells both in vitro and in xenograft models in vivo . We also found that MTA2 is transcriptionally upregulated by HIF‐1α through a hypoxia response element (HRE) of the MTA2 promoter in response to hypoxia. Reciprocally, MTA2 deacetylates HIF‐1α and enhances its stability through interacting with histone deacetylase 1 (HDAC1). Consequently, HIF‐1α recruits MTA2 and HDAC1 to the HRE of the E‐cadherin promoter, by which E‐cadherin transcription is repressed. In agreement with these experimental results, MTA2 is positively associated with HIF‐1α, but inversely correlated with E‐cadherin, in pancreatic carcinoma samples. Moreover, data from The Cancer Genome Atlas on 172 pancreatic carcinomas indicate an association between high expression of MTA2 and short overall survival. Taken together, our study identifies MTA2 as a critical hub and potential therapeutic target to inhibit the progression and metastasis of pancreatic carcinoma. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.